It’s not just droplets: a systematic review and meta-analysis of the modes of transmission of Group A Streptococcus - Barth, Dylan D.; Daw, Jessica; Enkel, Stephanie L.; McRae, Tracy; Carapetis, Jonathan R.; Wyber, Rosemary; Bowen, Asha C.; Engel, Mark E. (Frontiers in Public Health, 2025)
BackgroundThe transmission of Group A Streptococcus (Strep A) through respiratory droplets has been considered the dominant mode of transmission to date; however, little is known about the relative contribution of other modes of transmission. This review systematically summarises the contemporary evidence regarding the transmission of Strep A.MethodsA comprehensive search strategy was implemented to identify studies on Strep A transmission published in English between 1980 and 2019. Full-text articles were screened and included based on the predefined criteria. Studies were included if molecular techniques were used to identify the same Strep A strain in both clinical and environmental swabs. A random-effects meta-analysis model was used to aggregate attack rate estimates with 95% confidence intervals (CI), incorporating the Freeman–Tukey transformation to account for variability between studies.ResultsA total of 34 transmission cohorts were included in this study. The overall attack rate of Strep A was 18.4% (95% CI, 13.1–24.2%, I2 = 95.9%), for direct contact, it was 20.5% (95% CI, 8.3–35.4%), and for indirect contact, it was 19.1% (95% CI, 13.2–25.7%). When pooled by geographical location, the attack rate was 30.38% (95% CI, 20.89–40.75%) in non-urban settings and 7.36% (95% CI, 2.60–14.21%) in urban settings.ConclusionDirect contact is no longer the dominant form of Strep A transmission. Our contemporary findings have implications for the development of evidence-based environmental health strategies aimed at reducing Strep A transmission.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42019138472, CRD42019138472.